Keep the bedtime story: A daily reading ritual improves empathy and creativity in children - Maeve Winter; A. J. Willy; James Ingersoll; Michael Joseph Meyer; Erin B. D. Clabough (PLoS ONE, 2026)
Creativity and empathy are interconnected skills that have shown concerning declines in young people, yet both can be enhanced through practice-based interventions. We examined whether a two-week nightly bedtime reading routine could improve empathy and creativity in children aged 6–8 (N = 38). Participants were randomly assigned to either read picture books straight through or pause at a conflict point to ask two reflection questions about characters’ feelings and potential actions. Children completed measures of empathy (modified Interpersonal Reactivity Index) and creativity (Wallach-Kogan Alternative Uses Test) before and after the intervention. Both groups showed significant improvements in cognitive empathy, total empathy, creative fluency, and creative originality, regardless of the reflection condition. However, children in the pause group demonstrated significantly greater gains in creative fluency compared to the read-through group. Older children showed lower creative originality than younger children, with no sex differences observed. These findings suggest that consistent bedtime reading—with or without structured reflection—may enhance empathy and creativity in young children, providing families with an accessible intervention to counter societal declines in these critical skills.